2019
DOI: 10.3390/met9060697
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Surface Quality Improvements in the Manufacturing of Ti-6Al-4V Parts Using Hot Single Point Incremental Forming

Abstract: The present work focuses on the manufacturing of Ti-6Al-4V parts using hot single point incremental forming (SPIF), a non-conventional forming technology mainly oriented toward the fabrication of prototypes, spare parts, or very low volume series. In the used procedure, the entire sheet is heated and kept at uniform temperature while the tool incrementally forms the part, with the limited accuracy of the obtained parts being the major drawback of the process. Thus, this work proposes two approaches to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Figure 9 shows the evolution of the experimental and numerical axial forming force during the process for the cones formed at different wall angles (a) α = 45°, (b) α = 50°, (c) α = 53°, (d) α = 55° and (e) α = 57°. As several authors have observed, the maximum forming force increases when the wall angle increases [15,30]. As can be observed, the computed axial force is in close agreement with the efforts recorded experimentally for all the assays.…”
Section: Warm Spif Parameters Measurementsupporting
confidence: 88%
“…Figure 9 shows the evolution of the experimental and numerical axial forming force during the process for the cones formed at different wall angles (a) α = 45°, (b) α = 50°, (c) α = 53°, (d) α = 55° and (e) α = 57°. As several authors have observed, the maximum forming force increases when the wall angle increases [15,30]. As can be observed, the computed axial force is in close agreement with the efforts recorded experimentally for all the assays.…”
Section: Warm Spif Parameters Measurementsupporting
confidence: 88%
“…Ambrogio et al [10] designed an external heating system using electric bands. Similar systems have been applied by Naranjo et al [11] and Ortiz et al [12]. There have been attempts to improve formability using the local heating generated between the tool friction on the sheet metal when it rotates at high speed [13].…”
Section: Introductionmentioning
confidence: 97%
“…As an example, Duflou et al [14] used dynamic local heating of the sheet material by means of a laser beam applied to the contact zone simultaneously with the forming tool, on the opposite side of the part. Multiple other material heating methods were used over time, with positive results on the part dimensional accuracy, as follows [15]: friction heating a high tool rotational speed of the tool [16], electric heating [17], induction heating [18], warming sheet material by using hot air blowers [19] or hot fluids [20], using a furnace [21] or even combinations of the above methods [22]. Although the improvements due to local or global material heating are confirmed, such methods require auxiliary heating equipment that can be expensive and difficult to handle, and more importantly entail significant energy consumption during forming.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, mixed strategies are also presented, combined to improve part dimensional accuracy. An example of a hybrid strategy is offed by Ortiz et al [21] in their research on manufacturing aircraft parts from titanium alloy; a mix of three solutions is needed to improve geometric accuracy. The first solution is a special clamping device that allows heating of the sheet blank by means of a 10 kW furnace.…”
Section: Introductionmentioning
confidence: 99%